ANALISIS KANDUNGAN LEMAK BABI DALAM PRODUK PANGAN DI PADANGSIDIMPUAN SECARA KUALITATIF DENGAN MENGGUNAKAN - Hilda, Lelya (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
Halal food issue is an urgent problem in the community . One of the factors causing this issue , among others, is the lack of attention and supervision from the government to the manufacturer who is engaged in processing and food supply. The problems of this research is What food product has been contaminated Padangsidimpuan circulating in pig fat ? While the purpose of this study to determine what food products contain fat Padangsidimpuan circulating in pigs. Determination of lard is done qualitatively using Gas Chromatography ( GC). The products analyzed are products suspected to contain lard because of the issues or people would doubt the outstanding products . Of some food products analyzed are shredded cake , meatballs , burgers risol and proved that the product does not contain lard indicated that the physico-chemical testing , GC - MS on a pig fat / pork negative . shreddedcake, risol and derived from chicken fat burgers , meatballs while derived from beef tallow . News is circulating in the community could be an invention of people because of trade competition or of outstanding products is still dominated by Chinese or non-Muslims and outstanding products are also no halal label . Halal food is not only seen from the absence of lard / derivatives but also seen where obtained / source , process or processing .